(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of this study is to explore the newspaper reading habits of college students studying in undergraduate and postgraduate of Arts faculty. Reading newspaper is one of the best ways to keep up- to- date with the ever advancing world. Its aim is to determine the effects of widespread use of newspaper in reading habits, all the important news and events of the world are brought to our door - step by the newspaper.